2006
DOI: 10.2528/pier06052601
|View full text |Cite
|
Sign up to set email alerts
|

A Maxwell Garnett Model for Dielectric Mixtures Containing Conducting Particles at Optical Frequencies

Abstract: Abstract-Mathematical modeling of composites made of a dielectric base and randomly oriented metal inclusions is considered. Different sources of frequency-dependent metal conductivity at optical frequencies are taken into account. These include the skin-effect, dimensional (length-size) resonance of metal particles, and the Drude model. Also, the mean free path of electrons in metals can be smaller than the characteristic sizes of nanoparticles, and this leads to the decrease in conductivity of the metal incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 13 publications
3
83
0
Order By: Relevance
“…Bruggeman theory enables one to avoid the uncertainty connected to the choice of background medium that is inherent in the Maxwell-Garnett treatment. 53 The Bruggeman model was found to accurately predict the dielectric constants of two-phase dielectric mixtures in a wide range of compositions.…”
Section: Theory and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruggeman theory enables one to avoid the uncertainty connected to the choice of background medium that is inherent in the Maxwell-Garnett treatment. 53 The Bruggeman model was found to accurately predict the dielectric constants of two-phase dielectric mixtures in a wide range of compositions.…”
Section: Theory and Discussionmentioning
confidence: 99%
“…Various models in the past considered the effective dielectric response of heterogeneous mixtures in terms of permittivity, volume fractions, and geometry of the initial components. [51][52][53] The formulae provided in these reports are based on distinct structure of a mixture; therefore the validity is determined by how closely the models describe the actual structure. In this work, a model for the dielectric response of the NFO-BTO core-shell structure and its variation with applied magnetic field is discussed.…”
Section: Theory and Discussionmentioning
confidence: 99%
“…These materials allow for high design flexibility, since they can be adapted to achieve complex shapes and ad-hoc strength levels, provide sound and heat isolations, as well as good electromagnetic shielding protection [3][4][5][6][7]. Micro/nano fabrication processes, indeed, allow for making composites of carbon nanotubes, which could be used in various devices, e.g., actuators [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In our paper [27], it has been shown that the MG formulation can be used at optical frequencies to predict frequency characteristics of composites containing conductive inclusions (nanorods). In [27], several subtle effects, such as the skin effect in conducting inclusions, the Drude frequency dependence of metals, the effect of the mean free path in small-size conducting inclusions, as well as the dimensional resonances in the nanorods, have been taken into account.…”
Section: Introductionmentioning
confidence: 99%